LEFT VENTRICULAR SYSTOLIC DYSFUNCTION IN PREGNANT WOMEN WITH PRE-ECLAMPSIA WITHOUT PROTEINURIA - Kamolova Diyora Jamshedovna,Khusainova Munira Alisherovna,Khaydarova Zarrina Erkinovna,Makhmudova Khanuza Davranovna (Journals Park Publishing, 2022)
The article presents the main pathophysiological mechanisms associated with the development of pregnancy complications on the background of arterial hypertension in patients without clinical manifestations of left ventricular dysfunction, shows the possibilities of speckle-tracking echocardiography in detecting latent systolic dysfunction of the left ventricle in pregnant women on the background of preeclampsia, not accompanied by proteinuria.
Keywords: preeclampsia, arterial hypertension, myocardial deformity, speckle-tracking echocardiography, ejection fraction, proteinuria.